Clinical anatomy : applied anatomy for students and junior doctors / Harold Ellis, Vishy Mahadevan - Ellis, Harold
FIRST PUBLISHED IN 1960 Written by one of the great teachers of anatomy, the thirteenth edition of Clinical Anatomy continues to provide thousands of medical students, postgraduate trainees and junior doctors across the world with essential anatomical information within a clinical setting. It is particularly appropriate for those preparing for the Intercollegiate Membership Examination of the Royal Colleges of Surgeons (I-MRCS). Professor Harold Ellis is again joined by Professor Vishy Mahadevan to provide detailed, easy-to-follow structured text suitable for anatomy students and trainees of all levels. Fully revised and updated with many new illustrations, this new edition features for the first time, several anatomical drawings overlaid on a living anatomy model to provide detailed topographical orientation and accurate surface representation. The companion website at www.ellisclinicalanatomy.co.uk/13edition contains digital flashcards of all the illustrations and photographs contained in the book – ideal for revision and teaching purposes.